Contrast in the density and biomass of fish in a reef system with different fishing intensity in the Mexican Caribbean - José Manuel Castro-Pérez; Carmen Amelia Villegas-Sánchez; Alejandro Medina-Quej; Rigoberto Rosas-Luis; Jesús E. Arias-González (PeerJ)
A wide range of fish species are caught in reef fisheries. However, fishing efforts tend to be highly selective in favor of large species, which generally have low population growth rates, making them more vulnerable to overfishing. When the decline of large predators occurs, fishing efforts start to focus on catching species from lower trophic levels, which can cause a trophic cascade effect. The objective of this research was to detect changes in the density and biomass of fish communities in areas with different fishing intensity in the study area. This study was carried out in the Banco Chinchorro Biosphere (BCBR) in the Mexican Caribbean and analyze the effect of fishing intensity on fish density and biomass, comparing data obtained from visual censuses with dependent information of the fishery. Evidence was found of a relationship between high fishing exploitation and low levels of density and biomass for Epinephelus striatus, E. guttatus and Lachnolaimus maximus. The decline of predators had no evident effect on the density and biomass of non-commercially important species. The density and biomass of commercially important fish species were influenced by the presence of algae, octocorals, hydrocorals and by variations in their catch per unit of effort (CPUE). This study detected that density and biomass have decreased in some species belonging to the Serranidae and Lutjanidae families in areas with high fishing intensity. On the other hand, little evidence was found that the density and total biomass of families of noncommercially important species increased through the decline of their predators. These results are consistent with previous work documenting how fishing activity affects fish species with high trophic levels. The information generated will help the Reserve’s managers make decisions towards better management and conservation of fishery resources.